1998
DOI: 10.1021/es980114z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Triorganotin Compounds with Dissolved Humic Acids

Abstract: Sorption to dissolved organic matter (DOM) may influence significantly the fate and the effects of organic pollutants in the aquatic environment. To date, most studies on DOMwater partitioning have focused on neutral hydrophobic compounds. Very little is known on the binding of hydrophobic organic cations to DOM. In this study, the association of triorganotin compounds (TOTs) with dissolved Aldrich and Suwannee River humic acids has been systematically investigated as a function of pH and sodium perchlorate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
74
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 35 publications
9
74
0
1
Order By: Relevance
“…First, methyltins can reacts with humic acid to form polymeric species (Omar and Bowen, 1982) as humic acid, a ubiquitous class of electrolytes, can form the complexes with organotin compounds in natural waters through chelation and hydrogen bonding (Oloughlin et al, 2000;Giacalone et al, 2006), which influence strongly the degradation rates of methyltins. For example, Arnold et al (1998) found that triorganotin cation can form the complexes with negatively charged ligands (i.e., carboxylate and phenolate groups) of the humic acids over the pH range 5.7-9.3. Second, humic acid and its UV degradation products (Garbin et al, 2007) can bind with free radicals and thus function as a powerful free radical scavenger.…”
Section: Effect Of Humic Acid On Degradationmentioning
confidence: 99%
“…First, methyltins can reacts with humic acid to form polymeric species (Omar and Bowen, 1982) as humic acid, a ubiquitous class of electrolytes, can form the complexes with organotin compounds in natural waters through chelation and hydrogen bonding (Oloughlin et al, 2000;Giacalone et al, 2006), which influence strongly the degradation rates of methyltins. For example, Arnold et al (1998) found that triorganotin cation can form the complexes with negatively charged ligands (i.e., carboxylate and phenolate groups) of the humic acids over the pH range 5.7-9.3. Second, humic acid and its UV degradation products (Garbin et al, 2007) can bind with free radicals and thus function as a powerful free radical scavenger.…”
Section: Effect Of Humic Acid On Degradationmentioning
confidence: 99%
“…Schwarzenbach and co-workers investigated the partition in liposome-water system of a series of substituted phenols and anilines with pH dependent results (Escher and Schwarzenbach, 1996;Escher et al, 2002) and Arnold et al also found that the association of triorganotin compounds with dissolved humic acids was strongly pH dependent (Arnold et al, 1998). A few studies on the association of chlorophenols with various DOM were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption using sorbents is among the widely employed methods to remove pollutants. Systematic examinations of the adsorption of TBT on various absorbents like natural sediments [11][12][13], pure minerals [14,15], organic matters [16] and black carbons [13,17] have been carried out.…”
Section: Introductionmentioning
confidence: 99%